Prevention of depression and anxiety in later life: design of a randomized controlled trial for the clinical and economic evaluation of a life-review intervention - Smit Filip; Bohlmeijer Ernst T; Korte Jojanneke (BMC, 2009)
Abstract Background Depressive and anxiety symptoms in older adults could develop into significant health problems with detrimental effects on quality of life and a possibly poor prognosis. Therefore, there is a need for preventive interventions which are at once effective, acceptable and economic affordable. Methods and design This paper describes the design of a study evaluating "The stories we live by", a preventive life-review group intervention, which was recently developed for adults of 55 years and over with depressive and anxiety symptoms. Both clinical and economic effectiveness will be evaluated in a pragmatic randomized controlled trial. The participants in the intervention condition will receive the 8-session preventive intervention. The participants in the control condition will have access to usual care. Clinical end-terms are depressive and anxiety symptoms, current major depressive episode, quality of life and positive mental health post-treatment (3 months after baseline) and at follow-ups (6 and 12 months after baseline). Additional goals of this study are to identify groups for whom the intervention is particularly effective and to identify the therapeutic pathways that are vital in inducing clinical change. This will be done by analyzing if treatment response is moderated by demographics, personality, past major depressive episodes, important life events and chronically disease, and mediated by reminiscence functions, perceived control, automatic positive thoughts and meaning in life. Finally the cost-effectiveness of the intervention relative to care as usual will be assessed by computing incremental costs per case of depression and anxiety avoided (cost-effectiveness) and per quality adjusted life year (QALY) (cost utility). Discussion It is expected that both the life-review intervention and its evaluation will contribute to the existing body of knowledge in several ways. First, the intervention is unique in linking life-review with narrative therapy and in its focus on specific, positive memories. Second, the evaluation is likely to answer questions regarding the acceptability and cost-effectiveness of life-review that have not been addressed thoroughly until now. Positive results of this study will make available a new evidence-based intervention to improve public health among people of 55 years and over. Trial registration Nederlands Trial Register TC = 1860.